Research on User Demands and Functional Design of an AR-Based Interior Design and Display Platform for Recreational Vehicles - Xun Zhang; Xiyu Wang; Wei Xu (Applied Sciences)
Background: Augmented Reality (AR) technology provides a new way for product design and display due to its unique interaction, enabling customers to experience products more comprehensively and immersively. Objective: To study the interactive form and application of AR technology in the interior design and display of RV, to provide new ideas and solutions for the interior design of RV, to optimize the user experience of customers and improve the work efficiency in the process of customized interior design of RV. Methods: Qualitative and quantitative research methods were adopted, the target customer groups were investigated based on the KANO model, the data were analysed, and the design suggestions for the function and interactive interface of the RV interior design display platform were summarized. Results: Based on the investigation and research, the specific functions of the RV indoor experience design platform and the needs of the target user groups were identified, including 12 essential needs, 5 charm needs, 1 expectation needs and 2 undifferentiated needs, which correspond to different functions, respectively. Finally, the main features of the platform are outlined, and the functional framework of the RV interior design and display platform is drawn. Conclusions: The interactive form of AR RV interior design includes user interface design and interactive mode design, which can greatly enhance user experience, optimize space utilization and enhance customized services. The application of AR technology in RV design has a high potential, providing theoretical and practical support for the design and development of the RV AR RV design display platform.